A rare case report of renal clear cell carcinoma with multiple skin metastases and a review of the literature - Wang, Wei; Kang, Yongcun; Qu, Xiaona; Li, Yang; Zhou, Hongyan (Frontiers in Oncology, 2024)
Renal cell carcinoma is the most common type of primary renal cancer, and clear cell carcinoma is the most common subtype, accounting for approximately 70% of all adult renal cell carcinoma cases. At the time of diagnosis, many patients already have metastatic manifestations. Cutaneous metastasis of renal clear cell carcinoma is very rare and usually represents a poor prognosis, mostly affecting the head and neck. In this paper, we report a case of renal clear cell carcinoma with multiple cutaneous metastases, including a chest wall mass for more than 10 years and an abdominal wall mass for 1 year. A 69-year-old man with a history of diabetes mellitus was admitted to the hospital for examination of a right chest and abdominal wall mass and peripheral pain, and ultrasonography suggested a solid space-occupying lesion in the left kidney, which was considered malignant, and a solid mass in the right chest and abdominal wall, which was considered metastatic. A subsequent abdominal CT scan showed malignant tumors in the left kidney and adrenal region, and multiple metastatic tumors in the liver, pancreas, right thoracoabdominal wall, and the abdomen. To clarify the nature of the pathology, an ultrasound-guided puncture of the right abdominal wall mass was performed, and the pathological diagnosis was clear cell carcinoma, with immunohistochemistry suggesting a renal clear cell carcinoma origin. The patient died within 6 months.